2017
DOI: 10.1007/s11011-017-9990-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of estrogen receptor β gene methylation in autistic males in a Chinese Han population

Abstract: Autism spectrum disorder (ASD) is a neurodevelopment disorder with abnormalities of social interaction, communication and repetitive behaviors. The higher prevalence of ASD in men implies a potential relationship between sex hormones and ASD etiology. The ESR2 gene encodes estrogen receptor beta (ESR2) and plays an important role during brain development. A relationship between ESR2 and ASD has been suggested by studies on single nucleotide polymorphisms and mRNA and protein expression levels in ASD patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Genome‐wide methylation analysis from peripheral blood of autistic individuals and controls showed significant hypermethylation . A similar observation of hypermethylation was observed in males with autism . Both of these studies were done in Chinese population.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Genome‐wide methylation analysis from peripheral blood of autistic individuals and controls showed significant hypermethylation . A similar observation of hypermethylation was observed in males with autism . Both of these studies were done in Chinese population.…”
Section: Discussionsupporting
confidence: 66%
“…Genome‐wide methylation analysis from peripheral blood cells of autistic individuals also shows significant hypermethylation . While another study reported hypermethylation only in males with autism . None of these studies have investigated whether the altered states of methylations are due to the impact of environment or based on the genetic variants in the methyltransferases that modulate the host response.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic mutations in the RELN gene and altered reelin pathways have been associated with several neurological disorders, including schizophrenia, bipolar disorder, depression, and ASD, and altered methylation levels of the RELN gene have been found in the postmortem brain tissues of post-puberal and adult ASD patients [59][60][61]. According to data obtained by Gallo et al [38], the peripheral methylation levels of another gene, ESR2, have also been associated with ASD severity as evaluated by the Children's Autism Rating Scale [48]. Another study included in the current review observed increased NGF (encoding the nerve growth factor) methylation levels in the peripheral blood of ASD individuals without mental regression during the first two years of life compared both to TD individuals and to ASD patients who develop mental regression [39].…”
Section: Discussionmentioning
confidence: 98%
“…Zhao et al investigated the methylation patterns of TGFB1, BAX, IGFBP3, PRKCB, PSEN2, and CCL2 in the peripheral blood of 42 ASD patients and 26 TD patients, finding that the rate of the methylation of TGFB1 was decreased in ASD and was positively associated with the interaction ability score [50]. One study used the BSP technique to investigate the methylation levels of the ESR2 gene in the peripheral blood of 54 ASD and 54 TD individuals, observing that 8 CpG sites in the ESR2 5 -flanking region were hypermethylated in ASD subjects and that 4 CpG sites were positively associated with the severity of the symptoms [48].…”
Section: Main Dna Methylation Findingsmentioning
confidence: 99%